Energy Systems Integration: Implications for public policy - Carlo Cambini; Raffaele Congiu; Tooraj Jamasb; Manuel Llorca; Golnoush Soroush (Copenhagen Business School (CBS), Department of Economics, 2020)
Energy Systems Integration (ESI) is an emerging paradigm and at the centre of the EU energy debate. ESI takes a holistic view of the electricity, gas and heat sectors to deliver a clean, reliable and affordable energy system. By identifying and exploiting the synergies within and between the sectors, ESI aims to increase flexibility in the energy system, maximize the integration of renewable energy and distributed generation, and reduce environmental impact. While ESI-enabling technologies have been studied from a technical perspective, the economic, regulatory and policy dimensions of ESI are yet to be analysed. This paper discusses ESI in a multi-step approach. We first focus on the economics of ESI-enabling technologies. We briefly discuss how the EU national regulators incentivise their adoption. We identify major economic and policy barriers to ESI and propose policy solutions to overcome these barriers. We conclude that current regulatory frameworks in the EU do not stimulate sufficient ESI investments and only through proper design of incentives the ESI paradigm could be achieved.
hdl:10398/9793
Keywords: L51; L94; Q4; 330; energy systems integration; sector coupling; regulation; innovation; research and development; economic and policy barriers